Synthesis of rocaglamide derivatives and evaluation of their Wnt signal inhibitory activities. Issue 11 (19th February 2016) - Arai, Midori A.; Kofuji, Yuuki; Tanaka, Yuuki; Yanase, Natsuki; Yamaku, Kazuki; Fuentes, Rolly G.; Karmakar, Utpal Kumar; Ishibashi, Masami
Abstract : A new class of rocaglamide derivatives were synthesized by [3 + 2] cycloaddition and their Wnt signal inhibitory activities were evaluated. Abstract : Rocaglamides are bioactive natural compounds which have a cyclopenta[ b ]benzofuran core structure. The total synthesis of a reported natural product, 3′-hydroxymethylrocaglate (5 ), was achieved using [3 + 2] cycloaddition between 3-hydroxyflavone and methyl cinnamate. We also describe the synthesis of rocaglamide heterocycle derivatives and evaluate their Wnt signal inhibitory activities. Compounds4, 5, 22a, 22b, 22c and23c showed potent Wnt signal inhibitory activity.